Mapas de información colaborativa para la delimitación de predios, bicirrutas y sitios turísticos en Tunja, Boyacá - Romero-Hernández, Wilmer-Andrés; González-Sanabria, Juan-Sebastián; Güiza-Pinzón, Fabián-David (Revista Científica, 2022)
New technologies and technological advances have contributed to a greater interaction with platforms such as crowdmapping, which allow people or organizations to have an information flow with which they can make contributions through collaborative maps. In order to understand its applications and uses, a systematic review was conducted on the application and importance of crowdmapping and its contribution to the creation of maps in different sectors or areas of society. From this review, the usefulness and efficiency of this type of mapping was determined regarding the delimitation of properties and bike routes, as well as the geolocation of tourist sites in Tunja (Boyacá), so that anyone accessing the maps could participate, appropriate the information, and contribute according to their interests. Said implementation makes its contribution people to know and be able to guide and provide relevant information to both citizens and tourists on the different routes for bicycle users or tourist sites in the city. In these cases, such information is provided by people who have lived the experience and want to share it, thus creating collaborative maps in real time. As for these maps, it is important to validate all the information in order for it to be completely real and for this type of platform to generate confidence for later implementation in other projects with a social aim.